Changes in antioxidant enzyme activities in Pinus sylvestris and Larix decidua seedlings after Melolontha melolontha attack - Skwarek, Monika; Patykowski, Jacek; Witczak, Adrian (Leśne Prace Badawcze, 2017)
Plants are constantly exposed to the influence of biotic and abiotic stress factors that significantly affect the induction of resistance responses. Biotic factors include bacteria, fungi and insects such as the common cockchafer ( Melolontha melolontha ) that harm many tree species, including pine and larch. The adult beetles damage needles, while the larvae (grubs) feed on roots. The aim of the experiment was to determine how plants cope with the damage caused by these insects. The activity of antioxidant enzymes such as peroxidase (POD) and superoxide dismutase (SOD) were determined three and six weeks after the insect-induced damage and the results show that the peroxidase activity, as measured with guaiacol (GPOD), was higher in the damaged roots of larch. The POD activity measured with syringaldazine (SPOD) was slightly higher in damaged pine needles as well as pine roots. SOD activity was higher in the damaged roots of both species as compared to the needles. It is believed that changes in the activity of POD and SOD as well as the presence of another form of SOD in the roots of larch, indicate direct involvement of these enzymes in the plants’ response to damage caused by M. melolontha .